The Legal Responsibility of Sport Trainers in Providing Health- Oriented Trainings and Nutritional Supplements - Ali Ramyar; Ehsan Moshkelgosha (Islamic Azad University, 2017)
Introduction: Regarding the prevalence of supplements and energizer drugs abuse and the civil and criminal responsibility of sports trainers in this regard, this study aimed to investigate the legal responsibility of sport trainers in providing health-oriented trainings and nutritional supplements. Methods: In this causal-comparative or post-hoc study, 101 volunteer trainers of sport clubs in Shiraz were selected as a cluster sampling. After explaining the purpose of the research, a researcher-made questionnaire (including 14 questions for assessing the sports trainers' awareness of their civil and criminal responsibility on nutritional supplements, whose validity had been approved by the professors of law and sports sciences) was completed and collected. To analyze the data, chi square test was run using SPSS 20 and Excel 2007 (p≤0.05). Results: The sports trainers are aware of the civil liability of the drugs prescribed in their sport fields (p=0.001), and awareness of the legal issues during the coaching course is gained, the same as awareness of civil liability (p=0.001). However, according to the trainers themselves, provision of legal training on civil liability for educators is necessary (p = 0.001). Conclusion: In general, it can be concluded that in spite of sports trainers' good knowledge and education about the civil liability of the abuse of nutritional supplements, the need for more educating legal issues is essential for trainers and athletes.